Speak for yourself - Johnson, Lana Wood (Scholastic Press, an imprint of Scholastic Inc., 2021)
Skylar Collins of Lovelace Academy intends to win at the Scholastic Exposition, (an extremely nerdy academic competition) using her latest app, which she considers a brilliant piece of coding; but first she has to assemble a team, and she will do anything to accomplish that, even if it means playing Cupid for teammates Joey and Zane--but her people skills are not as good as her coding, and when she starts to feel attracted to Zane things get even more complicated.